Biomimetic Hyaluronic Acid-Lysozyme Composite Coating on AZ31 Mg Alloy with Combined Antibacterial and Osteoinductive Activities - Hoey, David; Agarwal, Sankalp; Riffault, Mathieu; Duffy, Brendan; Curtin, James; Jaiswal, Swarna (My University, 2017)
This study presents the covalent grafting of a hyaluronic acid-lysozyme (HA-LZ) composite onto corrosion-resistant silane-coated AZ31 Mg alloy via EDC-NHS coupling reactions. The HA-LZ composite coatings created a smooth and hydrophilic surface with the increased concentration of functional lysozyme complexed to the hyaluronic acid. This was confirmed by the measurement of AFM, water contact angle, and quantification of hyaluronic acid and lysozyme. The colonization of S.aureus on HA-LZ composite-coated substrates was significantly reduced as compared to the hyaluronic acid, lysozyme coated and uncoated AZ31 controls. Such activity is due to the enhanced antibacterial activity of lysozyme component as observed from the spread plate assay, propidium iodide staining, and scanning electron microscopy. Furthermore, morphology of the osteoblast cells, alkaline phosphatase activity and DNA quantification studies demonstrated the improved biocompatibility and osteoinductive properties of HA-LZ-coated substrates. This was verified by comparing with the lysozyme coated and uncoated AZ31 substrates in terms of cell adhesion, proliferation, and differentiation of osteoblastic cells. Therefore, such multifunctional composite coatings with antibacterial and osteoinductive properties are promising can be potentially used for the surface modifications of orthopedic implants.
PUBLISHED
Keywords: Hylauronic acid-lysozyme; Corrosion resistant; Silane; Antibacterial and osteoinductive